De Sculptura : Wiener Festwochen. - Szeemann, Harald (Wien : Wiener Festwochen, 1986)
Adrian X, Robert ; Andre, Carl ; Beuys, Joseph ; Cragg, Tony ; dibbets, Jan ; Flavin, Dan ; Judd, Donald ; Kopf, Willi ; Laib, Wolfgang ; Long, Richard ; Merz, Mario ; Merz, Marisa ; Mucha, Reinhard ; Nauman, Bruce ; Opie, Julian ; Prantl, Karl ; Rabinowitch ; Rückriem, Ulrich ; Serra, Richard ; Twombly, Cy ; Virnich, Thomas ; Weinberger, Loïs ; West, Franz ; Zobernig, Heimo
De Sculptura : Wiener Festwochen im Messepalast, Wien, 16. Mai bis 20. Juli 1986
Duits
kunstcatalogus